The impact of ease of use and promotion through purchase intention on the purchase decision Shopeepay e-wallet in Jakarta - Maftuchach, Viniyati; Safitri, Kiki Eka (Privietlab, 2023)
The problem in this study is the effect of ease of use and promotion on purchasing decisions through purchase intention as an intervening variable and aims to determine the effect of ease of use and promotion on purchasing decisions through purchase intention as an intervening variable that is carried out on shopeepay e-wallet users in Jakarta. This research design is causal by using primary data. The population in this study is shopeepay users in the Jakarta area. The sampling technique in this study used a purposive sampling technique, namely the sampling method with certain criteria while the sample used was 87. For data processing using Smart PLS statistical software. The results showed that the ease of use had a significant effect on purchasing decisions, the promotion variable had a significant effect on purchasing decisions, the convenience variable had no significant effect on purchase intention, the promotion variable had a significant effect on purchase intention, and the purchase decision variable had a significant effect on purchase intention. Meanwhile, the ease of use variable does not have a significant effect on purchase intention through purchasing decisions. And for the promotion variable has a significant effect on purchase intention through purchasing decisions. Therefore, it is expected that the company can pay more attention to the factors that influence purchasing decisions in order to increase the company's revenue and be able to survive in today's tight competition.